2011
DOI: 10.1063/1.3625605
|View full text |Cite
|
Sign up to set email alerts
|

Organosilane deposition for microfluidic applications

Abstract: Treatment of surfaces to change the interaction of fluids with them is a critical step in constructing useful microfluidics devices, especially those used in biological applications. Silanization, the generic term applied to the formation of organosilane monolayers on substrates, is both widely reported in the literature and troublesome in actual application for the uninitiated. These monolayers can be subsequently modified to produce a surface of a specific functionality. Here various organosilane deposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 61 publications
0
65
0
Order By: Relevance
“…It will be an important research path in terms of stating the initial growth kinetics of octylsilane on a silica substrate for various applications like bio/nanosensors, preparing protective coatings, drug delivery, and microfluidics etc. [2,32,33]. The data obtained from all three studies were used for determining rate kinetics of molecular attachment and further re-orientation on a silica substrate.…”
Section: Introductionmentioning
confidence: 99%
“…It will be an important research path in terms of stating the initial growth kinetics of octylsilane on a silica substrate for various applications like bio/nanosensors, preparing protective coatings, drug delivery, and microfluidics etc. [2,32,33]. The data obtained from all three studies were used for determining rate kinetics of molecular attachment and further re-orientation on a silica substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its suitability to rapid prototyping, PDMS is one of the most commonly used materials for microfluidic systems. It is sometimes required that microchannel surfaces be modified to exhibit certain properties or functional groups, which can be achieved by techniques, such as organosilanes deposition (Glass et al, 2011;Pallandre et al, 2006). Several methods are also available for pumping solutions through microfluidic channels, but the most common are hydrodynamic and electroosmotic flow (EOF)-based pumping (Au et al, 2011).…”
Section: Biofilm Microfluidic Devicesmentioning
confidence: 99%
“…[12][13][14] The Octadecyltrichlorosilane (ODTS, Cl 3 Si (CH 3 ) 17 ), self-assembled monolayer (SAM) is one such organosilane used for realizing superhydrophobic surfaces [15,16] and this has been widely investigated on silicon surface, because of its wide range of applications in molecular electronics devices and microfluidics. [17][18][19][20][21] The superhydrophobicity of silicon surfaces achieved using the chemical texturing followed by chemical modification with depositions of SAM has been reported in literature. Mazur et al had shown the silicon texturing using laser followed by silane monolayer to obtain the Ξ c equal to 160°.…”
Section: Introductionmentioning
confidence: 99%